Upaya Guru dalam Meningkatkan Prestasi Belajar Siswa pada Mata Pelajaran PAI di SMA Almaarif Singosari Malang - Sifaul Liulil Absor; Ilyas Thohari; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Achieving a success of learning does not escape the learningobjectitself, namely students. in Al-Maarif Singosari High School students in learning Islamic Education include, the characteristics of PAI subject matter in the form of memorization are still complained by students, Interest inlearning achievement andthe efforts made by the teacher in improving student learning towards PAI subjects is still relatively low, and there are still many students who do not listen to their teachers because they are bored with material taught. And later this will greatly affect the achievements obtained by students. The purpose of this study is to describe the conditions of student learning achievement in AlMaarif Singosari Islamic High School. The methodused in this study is a qualitative method and the data collection technique in qualitative research consists of 3 techniques, namely observation, interview and documentation. In learning Islamic Education the average student gets diverse scores, some are good, some are lacking. The majority of good PAI values are obtained by students who live in the cottage, but different from the PAI values obtained by home students, they are more difficult to obtain good PAI scores. efforts made by teachers in improving student learningachievement on PAI subjects in Singosari Almaarif Islamic High School include; giving motivation, using various media in teaching, and also adding lessons.